2013
DOI: 10.1016/j.juro.2012.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Sperm During Microdissection Testicular Sperm Extraction in Men with Nonobstructive Azoospermia

Abstract: More than a third of the men with nonobstructive azoospermia required complete microdissection of the testes to identify sperm. Sperm were found on the contralateral side in up to 8% of the men in whom no sperm were identified in the initial testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
5
33
0
Order By: Relevance
“…Two of the men who underwent a bilateral micro-TESE had no spermatozoa identified intra-operatively but were subsequently found to have spermatozoa on final assessment (and had successful ICSI). These data indicate that a negative intra-operative result after unilateral micro-TESE carries a poor prognosis (a 16% final sperm retrieval rate after bilateral micro-TESE) and are in keeping with prior reports (Ramasamy et al, 2011(Ramasamy et al, , 2013. Moreover, our data also indicate that a negative intra-operative result after a complete bilateral micro-TESE also carries a very poor prognosis [a 6% (2/36) final sperm retrieval rate] as previously reported (Ramasamy et al, 2011(Ramasamy et al, , 2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Two of the men who underwent a bilateral micro-TESE had no spermatozoa identified intra-operatively but were subsequently found to have spermatozoa on final assessment (and had successful ICSI). These data indicate that a negative intra-operative result after unilateral micro-TESE carries a poor prognosis (a 16% final sperm retrieval rate after bilateral micro-TESE) and are in keeping with prior reports (Ramasamy et al, 2011(Ramasamy et al, , 2013. Moreover, our data also indicate that a negative intra-operative result after a complete bilateral micro-TESE also carries a very poor prognosis [a 6% (2/36) final sperm retrieval rate] as previously reported (Ramasamy et al, 2011(Ramasamy et al, , 2013).…”
Section: Discussionsupporting
confidence: 91%
“…An intra-operative assessment of sperm recovery during micro-TESE is performed in many centers as it decreases the amount of testicular tissue extracted and may help avoid a contra-lateral micro-TESE (Ramasamy et al, 2013). However, it remains unclear to date whether there is a minimum number and quality (motile vs. non-motile) of spermatozoa that needs to be identified intra-operatively before one considers that the micro-TESE is successful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature shows the micro-TESE SRR to be between 38-63% in NOA patients [6][7][8][9] . Given the SRR results from this study particularly in men with normal range FSH ≤ 10IU/L, we found that TESA in our experience had similar results compared to micro-TESE.…”
Section: Discussionmentioning
confidence: 99%
“…TESA also requires less operating time than the more technically challenging micro-TESE [7] . Most cases of micro-TESA can take hours to obtain spermatozoa.…”
Section: Discussionmentioning
confidence: 99%